The Influence of Emotional Factors and Product Quality on Purchase Decisions PT. Kedaung Medan Industrial Ltd - Kennedy, Kennedy; Yhessa Devies; Stevany, Stevany; Mangasi Butar Butar; Robinhot Gultom (Sean Institute, 2025)
The purpose of this study is to determine the partial and simultaneous impact of the variable factors of PT. Kedaung Medan Industrial Ltd. This type of research is a quantitative method. The object of research in this study is consumers at PT. Kedaung Medan Industrial Ltd, totaling 100 people. The data analysis technique used is multiple linear regression analysis. Partially, this study has succeeded in proving that emotional factors and product quality have an influence on purchasing decisions. Likewise, this study has succeeded in simultaneously proving that emotional factors and product quality have a significant influence on purchasing decisions at PT. Kedaung Medan Industrial Ltd.